Pengaruh Pembelajaran Kreatif Dan Motivasi Terhadap Hasil Belajar PAK Siswa Kelas VII SMP N 3 Sipoholon Tahun 2023/2024 - Marco Stepanus Nainggolan; Andar G. Pasaribu; Oktober Tua Aritonang (Jurnal Pendidikan Agama dan Teologi, 2024)
The objectives of this research are 1) to determine the positive and significant influence of creative learning on student learning outcomes; 2) to determine the positive and significant influence of motivation on student learning outcomes, 3) to determine the positive and significant influence of Creative Learning and Motivation on the PAK Learning Outcomes of Class VII Students at SMPN 3 Sipoholon in 2023/2024. The method used in this research is an inferential quantitative method with an expo-facto correlational model. The population was all class VII students of SMP N 3 Sipoholon with a total of 79 people and a sample of 66 people was determined using the finite population formula. Data was collected using a closed questionnaire with 60 items. The results of data analysis show that: 1) the calculated F value > F table between Creative Learning and students' PAK learning outcomes is 31.298 > 3.15, thus it is known that there is an influence between Creative Learning and students' PAK learning outcomes, namely 32.8%, 2 ) calculated F value > F table between Providing motivation on students' PAK learning outcomes, namely 30.698 > 3.15, thus it is known that there is an influence between Providing motivation on students' PAK learning outcomes, namely 32.4%, 3) calculated F value > F The table between Creative Learning and Providing Motivation on the PAK learning outcomes of students is 21.736 >> 3.15, so it is known that there is an influence between Creative Learning and Providing Motivation on the PAK learning outcomes of Class VII SMP N 3 Sipcholon in 2023 2024, namely 40.8 % thus Ha is accepted and Ho is rejected.